Assessment of antibiotic resistance in bacteriophage-insensitive Klebsiella pneumoniae. (October 2019) - Uddin, Md Jalal; Kim, Beomseok; Dawan, Jirapat; Ding, Tian; Kim, Jin-Chul; Ahn, Juhee
Abstract: This study was design to evaluate the physiological properties of bacteriophage-insensitive Klebsiella pneumoniae (BIKP) mutants in association with the antibiotic cross-resistance, β-lactamase activity, and gene expression. Klebsiella pneumoniae ATCC 23357(KP WT ), ciprofloxacin-induced antibiotic-resistant K . pneumoniae ATCC 23357 (KP CIP ), and clinically isolated antibiotic-resistant K . pneumoniae 10263 (KP CLI ) were used to isolate BIKP mutants against KPB1, PBKP02, PBKP21, PBKP29, PBKP33, and PBKP35. PBKP35-induced mutants, including bacteriophage-insensitive K . pneumoniae ATCC 23357 (BIKP WT ), ciprofloxacin-induced K. pneumoniae ATCC 23357 (BIKP CIP ), and clinically isolated antibiotic-resistant K. pneumoniae CCARM 10263 (BIKP CLI ). BIKP WT, BIKP CIP, and BIKP CLI were resistant to Klebsiella bacteriophages, KPB1, PBKP02, PBKP21, PBKP29, and PBKP33. The antibiotic cross-resistance to cefotaxime, cephalothin, chloramphenicol, ciprofloxacin, erythromycin, kanamycin, levofloxacin, and nalidixic acid was observed in BIKP WT . The relative expression levels of vagC was increased by more than 8-folds in BIKP WT, corresponding to the increased β-lactamase activity. The aac(6′)-Ib-cr was overexpressed in BIKP mutants, responsible for aminoglycoside and quinolone resistance. The phage-resistant mutants decreased the antibiotic susceptibilities in association with β-lactamase activity and antibiotic resistance-related gene expression. The results pointed out the cross-resistance of BIKP mutants to antibiotics, which might be considered when applying for the therapeutic use of bacteriophage.